2011
DOI: 10.1074/jbc.m111.275974
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Sucrose Synthase-1 from Arabidopsis thaliana and Its Functional Implications

Abstract: Background: Sucrose flux in plants is partly achieved through sucrose synthesis and cleavage catalyzed by sucrose synthase. Results: The crystal structure of sucrose synthase from Arabidopsis thaliana has been determined. Conclusion: The x-ray structures provide insights into the enzymology and regulation of sucrose synthase. Significance: The structures suggest how sucrose synthase interacts with cellular targets, such as membranes, organelles, and cytoskeletal actin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 58 publications
5
102
0
1
Order By: Relevance
“…A similar result was observed in the complexes between ADP-Glc and EcGS (24), and between UDP-Glc and Arabidopsis thaliana sucrose synthase, a member of the retaining GT4 family (19). In those cases, however, the respective diphosphonucleoside moieties of the donor molecule were present in the active sites of the enzymes, although not covalently bound to the not precisely identified glucose derivative.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A similar result was observed in the complexes between ADP-Glc and EcGS (24), and between UDP-Glc and Arabidopsis thaliana sucrose synthase, a member of the retaining GT4 family (19). In those cases, however, the respective diphosphonucleoside moieties of the donor molecule were present in the active sites of the enzymes, although not covalently bound to the not precisely identified glucose derivative.…”
Section: Discussionsupporting
confidence: 70%
“…Further along these lines, the discrete existence of a short-lived ion pair intermediate in the reaction pathway (Fig. 1C), which would result from the asynchronous cleavage of the bond between the anomeric carbon and leaving group and the formation of the donor-acceptor bond, has been proposed (4,18,19). According to IUPAC recommendations, this stepwise mechanism would be represented by D N *A N , where the asterisk indicates the formation of a short-lived intermediate.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, understanding the catalysis and the regulation of sucrose synthase is of great significance. Recently, Zheng et al (23) reported the crystal structure of the Arabidopsis thaliana sucrose synthase in complex with UDP and fructose in a closed conformation. This enzyme is a homotetramer composed of four identical subunits of ϳ90 kDa and belongs to group 4 of the GT-B retaining glycosyltransferase family (http://www.cazy.org/GlycosylTransferases.html) (24).…”
mentioning
confidence: 99%
“…This enzyme is a homotetramer composed of four identical subunits of ϳ90 kDa and belongs to group 4 of the GT-B retaining glycosyltransferase family (http://www.cazy.org/GlycosylTransferases.html) (24). An S N i-like reaction mechanism has been proposed for this enzyme family (23)(24)(25).…”
mentioning
confidence: 99%
“…Cassava leaf SuS plays an important role in the distribution of the photosynthesized carbohydrate (Zheng et al, 2011), thereby affects the cassava tuber starch accumulation. The cassava leaf SuS synthesis and decomposing direction activities were determined during the growth period (Figure 1 and 2).…”
Section: The Time Course Of Cassava Leaf Sus Synthesis Direction and mentioning
confidence: 99%